Green Synthesis of Silver Nanoparticles Using Caulerpa racemosa Extract as Bioreductor: Characterization and Antibacterial Activity - Barleany, Dhena Ria; Selviroh, Selviroh; Saleh, Afiatta Ilhan; Pitaloka, Alia Badra; Gunawan, Akbar (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
Silver nanoparticles (AgNPs) have attracted much attention due to their broad antimicrobial properties and have found many applications in various fields. In the current study, AgNPs were synthesized using an environmentally friendly method by utilizing Caulerpa racemosa extract as a bioreduction agent. This study aims to investigate the formation of AgNPs mediated by Caulerpa racemosa extract and to observe their antimicrobial capability. The concentration of silver nitrate (AgNO3) was varied to investigate its influence on the shape, size, and uniformity of the silver particles formed. The Fourier Transform Infra-red (FT-IR) test results revealed that Caulerpa racemosa extract has an (-OH) functional group that reduces Ag+ ions to Ag0, making it effective as a bioreductor for AgNPs synthesis. The shape and size of AgNPs were examined using Scanning Electron Microscope (SEM), and the results confirmed that increasing AgNO concentration from 5 to 20 mM produced larger and agglomerated particles. Additionally, AgNPs inhibitory effect on the growth of pathogenic Escherechia coli (gram-negative bacteria) was evaluated using the well diffusion method. The findings showed that AgNPs improved the antibacterial properties when incorporated into chitosan-based film solution. This indicates that AgNPs exhibit strong antibacterial activity against gram-negative bacteria and hold promises for use in bio-related applications, including food packaging and biomedical uses